1954
DOI: 10.1007/bf01380921
|View full text |Cite
|
Sign up to set email alerts
|

Zum Problem der Beziehungen von Bakterienantigenen und blutgruppenspezifischen Substanzen

Abstract: A. ILLCHMANN-CHRIST und V. NAGEL.DaB zwischen Bakterienantigenen und blutgruppenspezifischen Substanzen, im besonderen dem Isoagglutinogen A, enge Korrelationen bestehen kSnnen, die in entscheidender Weise durch das heterogenetisehe Forssman-Antigen bestimmt sind, daft heute als gesiehert angesehen werden. Wit verweisen hier beispielsweise nur auf die von BAILY und SHOR~ festgestellte .~hnlichkeit zwischen der Karbohydratnatur der Blutgruppensubstanz A und den von AVER:f, HEIDELBERGER und GO~B~L in gewissen Pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1960
1960
1984
1984

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Illchmann-Christ and Nagel (1954) found that anti-A antibody was removed from 0 and B sera by staphylococci and postulated that staphylococci possessed an A-like receptor. If this were so, persons belonging to blood-group A might carry staphylococci in the nose more frequently than those of other groups or have an increased susceptibility to staphylococcal infections, owing to an inability to produce anti-A antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Illchmann-Christ and Nagel (1954) found that anti-A antibody was removed from 0 and B sera by staphylococci and postulated that staphylococci possessed an A-like receptor. If this were so, persons belonging to blood-group A might carry staphylococci in the nose more frequently than those of other groups or have an increased susceptibility to staphylococcal infections, owing to an inability to produce anti-A antibody.…”
Section: Discussionmentioning
confidence: 99%
“…No precipitation was seen with extracts of E. coli or Salmonella typhosa. There may be a connection with the serologic similarity demonstrated between staphylococci and L. nionocytogenes (100), glandular fever (23), and blood groups (39).…”
Section: Nucleoproteins Heterophile Antigensmentioning
confidence: 97%